Reimagining Healthcare Workers and COVID-19 in Demotivational Posters During Pandemic - O. Yu. Gukosyants (Научный диалог, 2023)
The study examines the metaphors presented in demotivational posters during the COVID-19 pandemic. Images related to healthcare workers and the coronavirus infection are identified. The iconic (and less frequently verbal) components of the demotivational posters are analyzed, which explicitly convey the author’s assessment of these objects and model their perception by the audience. The most frequent metaphors identified in the study include ‘virus as a monster’, ‘virus as a criminal’, ‘virus as a swamp’, ‘virus as shackles’, and ‘virus as a trap’ to represent the COVID-19 infection. Metaphors such as ‘doctor as a warrior’, ‘doctor as a superhero’, ‘doctor as a champion’, ‘doctor as a disinsector’, ‘doctor as a builder’, and ‘doctor as a guardian angel’ are used by the authors of the demotivational posters to represent healthcare workers. By demonstrating these metaphorical characteristics of the objects, the authors of the demotivational posters model the desired perception of these objects by the audience, emphasizing the speed of disease spread, its devastating impact, the importance of adhering to quarantine measures, and expressing gratitude and appreciation to healthcare workers for their selfless work and for saving patients’ lives.